Mobile Learning Based on Guided Inquiry: Optimization of Students’ Motivation - I Made Agus Wirawan; I Made Gede Sunarya; I Gusti Nyoman Tri Jayendra; Aan Yudianto (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The learning media must be able to guide the students in every stage of learning to improve the students' activity in learning. Based on this problem, this study aims to: (1) design and implement the application of Mobile-Based Learning Based Learning for Computer Assembly Learning in Class X TKJ SMK N 2 Seririt. (2) determine the students’ motivation to Mobile Learning Based Guided Inquiry Application for Computer Assembly Lesson in Class X TKJ SMK N 2 Seririt. The method used in this study was the Waterfall model. Subjects in this study were the students of class X TKJ SMK N 2 Seririt. The results of this study are applications that use the Java programming language with the editor of Android Studio. All the features contained in this educational media work well. Students’ motivation using Mobile Based Guided Inquiry for Computer Assembly Lesson in Class X TKJ SMK N 2 Seririt is in a very good category